2019
DOI: 10.3889/oamjms.2019.163
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Fibroid Embolization via Transradial versus Transfemoral Arterial Access: Technical Results

Abstract: AIM: This study was designed to compare the safety and feasibility of uterine fibroid embolisation (UFE) via transradial access (TRA) and transfemoral access (TFA). MATERIAL AND METHODS: A retrospective analysis was conducted for 2 cohorts: 13 cases with already established TFA (from February 2016 to September 2018) and the first 11 procedures performed via TRA (from October 2017 to October 2018). Indications for embolization included: heavy menstrual bleedings (n = 18), lower urinary tract symptoms (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Our experience agrees with Gjoreski, et al [1] in the comparison of routes used, where it was evident that the Trans-Femoral route in comparison to the Trans-radial one, took longer time to perform, was associated with more exposure to luoroscopy, increased demand on post procedure site physical pressure for hemostasis and possibly more length of hospital stay. In accordance, the trans-radial route gained increased popularity amongst the treating physicians as well as the patients.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our experience agrees with Gjoreski, et al [1] in the comparison of routes used, where it was evident that the Trans-Femoral route in comparison to the Trans-radial one, took longer time to perform, was associated with more exposure to luoroscopy, increased demand on post procedure site physical pressure for hemostasis and possibly more length of hospital stay. In accordance, the trans-radial route gained increased popularity amongst the treating physicians as well as the patients.…”
Section: Discussionsupporting
confidence: 91%
“…The length of hospital stay in our study was longer than other studies [1], and that can be explained by our strict adherence and following of the meticulous protocol of our institute provided for pain management and prophylactic measures set to avoid infection and thrombosis. However, with the good outcome, increased demand on the procedure and acquired experience, a shift to short hospital stays rather than the current prolonged one can be implemented in future.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…A retrospective study of TRA in uterine artery embolization by an experienced interventional radiology group found a 100% technical success rate with no major adverse complications recorded, including no radial artery occlusions at 1-month follow-up. Furthermore, a retrospective study completed by an interventional radiology group and gynecologic group also found that TRA had a 100% technical success rate in uterine fibroid embolization and determined that TRA (60.3 minutes) required less procedural time than TFA (72.4 minutes) [13]. Finally, it should be noted that intraoperative vascular consultation in TAH-BSO is a rare event and likely is unpreventable because it is dependent on the surgeon’s clinical assessment and intraoperative findings.…”
Section: Discussionmentioning
confidence: 99%